Gender and collective action: A conceptual framework for analysis - Pandolfelli, Lauren; Meinzen-Dick, Ruth S.; Dohrn, Stephan (International Food Policy Research Institute, 2007)
This paper presents a framework for investigating the intersection of collective action and gender; i.e. how gender-oriented analysis can foster more effective collective action in the context of agriculture and natural resource management and how collective action can be used as a vehicle for gender equity. We begin with definitions of the key concepts and then present three entry points for a gendered analysis of collective action-motivations, effectiveness, and impact on gender equity- vis-à-vis the Institutional Analysis and Development (IAD) framework(Oakerson 1992; Ostrom 1991). At the heart of this framework is the action arena, which is shaped by a host of initial conditions, including asset endowments, vulnerabilities, and legal and governance systems that influence a range of outcomes. Applying a gender lens to this framework, we present an analysis of how women and men experience the initial set of conditions differently and thus, have different motivations and capacities for engaging in collective action. Next, we look at how the gender composition of groups affects theeffectiveness of collective action, and finally, at the impact of collective action on gender equity and women’s empowerment. We conclude with a discussion of how this framework can improve our understanding of gender and collective action in order to facilitate more effective collective action while fostering gender equity.